Decision Support System for Determining Problematic Students Using the Analytic Network Process (ANP) Method - Nuraida, Fitri (Syntax Corporation Indonesia, 2024)
In the world of primary and secondary education in Indonesia, educational guidance and counseling services aim to help students become individuals who can overcome problems well. In general, teenage students cannot be separated from the problems they face, especially during the transition period because these problems can disrupt students' learning activities. Teacher Counseling Guidance (BK) or counselor is a teacher who is obliged to provide direction and guidance to students. One of the problems faced by schools is that it is difficult to determine quickly and precisely which students really need to be given direction and guidance immediately. In this research, a decision support system was created using the Analytical Network Process (ANP) method for problematic students who needed counseling services. ANP is a decision-making method that has many or multiple criteria and methods. The result of this research is a decision support system that can determine problematic students so that this system can help schools, especially guidance and counseling teachers/counselors, take the right approach to problematic students.